Immunolocalization of growth, inhibitory, and proliferative factors involved in initial ovarian folliculogenesis from adult common squirrel monkey (Saimiri collinsi) - Scalercio, Sarah Raphaella Rocha de Azevedo (SAGE Publications, 2020)
We performed an immunohistochemical (IHC) study to determine the follicular expression of growth differentiation factor 9 (GDF-9), anti-Mu?llerian hormone (AMH), Kit Ligand (KL), and c-Kit in squirrel monkey ovary. Ovarian tissue fragments from 4 squirrel monkeys were collected by laparotomy and processed for classical histology and IHC. Additionally, follicle development was assessed by Ki67 immunostaining to evaluate proliferative status of granulosa cells. A total of 4025 follicles were examined (1475 for classical histology and 2550 for immunohistochemistry). More than 80% of the evaluated follicles were morphologically normal. The GDF-9 protein was detectable in oocyte cytoplasm from primordial (100%), primary (99.1%), and secondary (100%) follicles. The AMH was not expressed in primordial follicles but just in few primary follicles (13.8%). On the other hand, it was highly expressed in granulosa cells from secondary follicles (67.9%). c-Kit, KL receptor, was found in the oolemma of primordial (100%), primary (100%), and secondary (100%) follicles. The KL expression was observed in oocytes and granulosa cells from primordial (94.9%), primary (91.6%) and secondary follicles (100%). Ki67 immunostaining was observed in granulosa cells from primary (5.7%) and secondary (54.8%) follicles but not in primordial follicles. In conclusion, we described the localization of GDF-9, KL, c-Kit, and Ki67 proteins and confirmed the presence of AMH protein in preantral follicles from squirrel monkey. Our results offer contribution for understanding of folliculogenesis in neotropical nonhuman primates. Moreover, these markers can be used to assess follicular viability and functionality after cryopreservation, transplantation, or in vitro culture of ovarian tissue.